Emerging possibilities and constraints to Papua New Guinean smallholder coffee producers entering the speciality coffee market - Murray-Prior, Roy; Batt, Peter (FAO-UN, 2007)
Papua New Guinea produces around 1 percent of the world's coffee, most of it Arabica. The average price it achieves for its coffee is below the price of many comparable Arabica-producing countries. Most of Papua New Guinea's coffee comes from smallholders producing parchment using a village-level, wet processing method. One of the major obstacles to the improvement of coffee quality in Papua New Guinea is the failure of the current marketing system to give the right price signals to growers, in terms of different prices for different qualities of parchment. The marketing system is highly competitive, with large numbers of traders and roadside buyers purchasing small quantities of parchment from smallholder coffee producers. Since many of the taste faults in coffee cannot be detected at the parchment stage it is not possible to reward smallholders who produce superior tasting coffee. Historically, two coffee chains have coexisted in the Papua New Guinea industry, with the plantation chains, a remnant of colonial occupation, producing higher quality coffee for the speciality market. In contrast, the smallholder chains produce coffee for the soluble market. While the market determines quality and hence price essentially by consistency of taste, the government regulated grading system for green bean determines quality by bean size and the level of defects. The two are not necessarily correlated. Furthermore, cultural differences between plantation farmers, exporters and smallholder farmers, contribute to the perception by smallholders that lower prices are due to excessive profits in the processing export sector rather than to any inherent problems with coffee quality. A number of solutions have begun to emerge which will be explored.